Effect of maternal height on the risk of caesarean section in singleton births: evidence from a large-scale survey in India - Himanshu Chaurasia; Strong P Marbaniang; Hemkhothang Lhungdim (BMJ Open)
Objective This study examines the association of maternal height with caesarean section (CS) in India. It is hypothesised that maternal height has no significant effect on the risk of undergoing caesarean section.Design A cross-sectional study based on a nationally representative large-scale survey data (National Family Health Survey-4), conducted in 2015–2016.Setting and participants Analysis is based on 125 936 women age 15–49 years, having singleton live births. Logistic regression has been performed to determine the contribution of maternal height to the ORs of CS birth, adjusting for other exposures. Restricted cubic spline was used as a smooth function to model the non-linear relationship between height and CS. Height data were decomposed using the restricted cubic spline with five knots located at the 5th, 27.5th, 50th, 72.5th and 95th, percentiles.Primary and secondary outcome measures The main outcome variable of interest in the study is CS. Maternal height is the key explanatory variable. Other explanatory variables are age, parity, sex of child, birth weight, wealth index, place of residence, place of child delivery and household health insurance status.Results The results reveal that the odds of undergoing CS significantly decrease with increase in maternal heights. Mothers with a height of 120 cm (adjusted OR (AOR): 5.08; 95% CI 3.83 to 6.74) were five times more likely, while mothers with height of 180 cm were 23% less likely (AOR: 0.77; 95% CI 0.62 to 0.95) to undergo CS as compared with mothers with height of 150 cm.Conclusions Shorter maternal height is linked to a higher risk of CS. Our findings could be used to argue for policies that target stunting in infant girls and avoid unnecessary CS, as there is potential effect on growth during adolescence and early adulthood, with the goal to increase their adult heights, thereby lowering their risk of CS and adverse delivery outcomes.